Analisis Kualitas Produk, Word of Mouth dan Promosi Terhadap Keputusan Pembelian pada Marketplaces Shopee - Umar Bakti; Hairudin Hairudin; Made Ayu Agustina (Strategic: Journal of Management Sciences, 2023)
This study aims to determine the effect of the variable partially and simultaneously between the variables of Product Quality, Word of Mouth and Promossion on Purchase Decisions on the Shopee Marketplace Case Study on Students of the Faculty of Business, Universitas Mitra Indonesia. The research methodology used is a quantitative approach with data collection methods using questionnaires. The population in this study were all active students of the Faculty of Business, Universitas Mitra Indonesia, namely 399 students and the sample was determined using a simple random sampling technique with the Slovin formula, 80 respondents were obtained for students using the Shopee Marketplace. Then the data obtained were analyzed using multiple linear regression analysis. The results showed that Word of Mouth partially had no effect on Shopee Marketplace Purchase Decisions, while Product Quality and Promossion partially had a positive and significant effect on Shopee Marketplace Purchase Decisions. While simultaneously Product Quality, Word of Mouth and Price affect the Purchase Decision on the Shopee Marketplace for Students of the Faculty of Business, Universitas Mitra Indonesia by 47.8%